2015
DOI: 10.1002/cncr.29379
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of meningiomas post‐Public Law 107‐206: The Benign Brain Tumor Cancer Registries Amendment Act

Abstract: Purpose Our analysis follows the implementation of Public Law 107–260, the Benign Brain Tumor Cancer Registries Act mandating collection of non-malignant brain tumors including meningiomas. Methods Meningiomas were selected from the Surveillance, Epidemiology, and End Results (SEER) Program database for 2004–2011. Demographic and clinical characteristics, initial treatment patterns, and survival outcomes were evaluated. Results The average annual age-adjusted incidence rates were 7.62 per 100,000 populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 32 publications
(55 reference statements)
4
55
1
2
Order By: Relevance
“…Also concordant with previous reports, black race and larger tumor size were found to be adverse prognostic factors. 3,22,23 Regarding lateralization, we found that the proportion of malignant/borderline malignant tumors was greater for bilateral meningiomas. This effect is presumably explained by size as bilateral tumors were on average larger (41.5 mm) than midline (30.0 mm) or unilateral (27.2 mm) tumors.…”
Section: Discussionmentioning
confidence: 80%
“…Also concordant with previous reports, black race and larger tumor size were found to be adverse prognostic factors. 3,22,23 Regarding lateralization, we found that the proportion of malignant/borderline malignant tumors was greater for bilateral meningiomas. This effect is presumably explained by size as bilateral tumors were on average larger (41.5 mm) than midline (30.0 mm) or unilateral (27.2 mm) tumors.…”
Section: Discussionmentioning
confidence: 80%
“…Meningiomas have become increasingly prevalent [21] in the United States as the general population ages and as the use of brain imaging has become more prevalent. While the majority of these tumors are benign with relatively good outcomes [22], a significant proportion are AMs with more aggressive pathology and worse outcomes [18,2325].…”
Section: Discussionmentioning
confidence: 99%
“…31 They are 3 times more common in females and are largely tumors of adulthood, with greater than 70% occurring after age 55. 31 Meningiomas are rarely seen in children unless syndromic or associated with radiation (less than 2% occur in patients 20 yr of age or younger). 32 With 15 subtypes in the 2007 WHO classification, they are histologically heterogeneous, although most (90%) are benign and classified as grade I.…”
Section: Meningiomamentioning
confidence: 99%